Scientific awakening: Interactive workshops with Engineering (Research, Society and Development, 2021)
The strengthening of relations between school entities and universities is beneficial for both sides and also for the local community, which is graced through the dissemination of scientific knowledge. The use of actions in the form of workshops and lectures that arouse students' interest in the technological area, since elementary school, led to the development of skills for the formation of the scientific being. The aim of this work was to arouse interest in students in the technological area, both for instigation and for the future insertion in the academic environment. To this end, the interaction of professors, undergraduate and graduate students from the Food Engineering and Chemical Engineering courses was promoted with students from the elementary schools in the municipal network. The lectures and practical workshops were held at the university where technological knowledge was discussed. After completing these actions, a questionnaire was applied in order to assess the students' approval and interest. These actions promoted among students the desire to experience the university, in addition to also serving to exchange pedagogical knowledge and teaching-learning between teachers, students, undergraduate and graduate students.